Perbandingan Kinerja Teknologi Streaming HTTP Pseudostreaming dan DASH pada Jaringan Area Kampus Gedung D dan E FILKOM UB - Sarah Fitriannisa Ruzis (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In its development, video streaming originally delivered videos to users without them being able to watch the videos while they were being downloaded. In a further development, users can watch a video they request while the video is in the progress of being downloaded, this method is called progressive download which does not support playback capabilities. To make up for this shortfall, the next streaming technology was developed, called packet loss, which enables seeking in the video timeline. The third streaming method that followed is called adaptive streaming, wherein this method is able to adjust the quality of video playback according to the network conditions of the user. In this research, we were implementing packet loss and DASH as streaming methods began by the encoding of a source video file with various levels of quality and bitrates. For DASH (Dynamic Adaptive Streaming over HTTP), segmentation and manifest file setup needed to be performed. The aim of this research is to compare the performance of two streaming methods, packet loss and adaptive streaming, which is conducted by observing the parameter of QoS (Quality of Service) on the network side and subjective assessment, which is then analyzed using the method of paired sample t-test.